Evaluation of Compounding Sterile Preparations for Hospitalized Pediatric Patients in "X" Hospital Semarang City, Indonesia - Melviya Sudianto; Dina Christin Ayuningputri; Sri Hartati Yuliani (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Compounding sterile preparation, especially for hospitalized pediatric patients, needs more concern due to dose adjustment. Things to be concerned about are compounding personnel, utilization of aseptic technique, and facilitation that affects the quality of sterile preparations. The aims of this study were to observe compounding process and to quality the sterile preparations for hospitalized pediatric patients in “X” Hospital, Semarang City, Indonesia. This research is an observational analitic with incidentally sampling research. Subject in this research was personnel who performed sterile preparations for hospitalized pediatric patients. Results from 114 sterile preparations which were observed in pediatric ward showed that compounding personnel (100%), facilities & infrastuctures, and sterile preparations procedure were not suitable with the Mixing Guideline for injectable drug and cytostatic (2009), hence it could impact the quality of sterile preparations. In addition, even after implementing appropriate solvent, compounding procedures, and aseptic technique had been utilized (100%), the physical incompatibility occurred was 8.77%. The pH of Ceftriaxone and Cefotaxime was similar with those in the literature, but for Omeprazole’s pH and based on sterility test, there were no bacterial growth.